2005
DOI: 10.1152/japplphysiol.01392.2004
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced oxidative stress leads hemolysis in sedentary but not trained humans

Abstract: Intravascular hemolysis is one of the most emphasized mechanisms for destruction of erythrocytes during and after physical activity. Exercise-induced oxidative stress has been proposed among the different factors for explaining exercise-induced hemolysis. The validity of oxidative stress following exhaustive cycling exercise on erythrocyte damage was investigated in sedentary and trained subjects before and after antioxidant vitamin treatment (A, C, and E) for 2 mo. Exercise induced a significant increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
3
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 36 publications
(47 reference statements)
7
65
3
12
Order By: Relevance
“…However after such an adaptation period, exercise was found to exert no significant increase on erythrocyte osmotic fragility (20). A similar situation was also observed in humans which shows exercise is beneficial for trained individuals but exerting untoward effect on sedentary ones (21). Our findings can be interpreted as insufficient adaptation of rats to exercise although a preparatory exercise period was administered prior to exercise.…”
Section: Discussionsupporting
confidence: 79%
“…However after such an adaptation period, exercise was found to exert no significant increase on erythrocyte osmotic fragility (20). A similar situation was also observed in humans which shows exercise is beneficial for trained individuals but exerting untoward effect on sedentary ones (21). Our findings can be interpreted as insufficient adaptation of rats to exercise although a preparatory exercise period was administered prior to exercise.…”
Section: Discussionsupporting
confidence: 79%
“…the breakdown of red blood cells (Lim et al, 2000). Exercise-induced haemolysis is well documented in humans (Sentürk et al, 2005), and has been suggested to occur in birds (Landys-Ciannelli et al, 2002;Piersma et al, 1996). If haptoglobin levels are depleted by binding to oxidative iron during migration, this may explain the decrease in haptoglobin we found with increasing flight duration.…”
Section: Discussionmentioning
confidence: 67%
“…Da mesma forma, Miyazaki et al (23) não observaram mudança nos marcadores de oxidação protéica, tanto após 12 semanas de treinamento quanto após exercício exaustivo, porém, avaliando sujeitos saudáveis, não atletas. Em outro modelo de exercício, Sentürk et al (24) , avaliando atletas em um teste incremental máximo, observaram dano às proteínas. Os atletas em nosso estudo não necessariamente chegaram à exaustão, tinham experiência de treinamento maior que 12 semanas e provavelmente mantiveram-se no metabolismo aeróbio a maior parte da competição, o que poderia explicar a diferença entre os resultados encontrados.…”
Section: Discussionunclassified
“…Sentürk et al (24) avaliaram os eritrócitos de indivíduos sedentários e atletas após um protocolo exaustivo em bicicleta, tanto antes quanto após um período de dois meses de suplementação com as vitaminas A, C e E. Os autores demonstraram que uma simples sessão de exercício intenso foi capaz de aumentar os parâmetros de estresse oxidativo e induzir deterioração da função e estrutura dos eritrócitos em sedentários, o que foi prevenido por dois meses de suplementação antioxidante. Contudo, esse comportamento não se repetiu nos indivíduos que eram treinados.…”
Section: Discussionunclassified